LA INSUFICIENCIA EN EL COOTAD, DE UNA NORMA LEGAL QUE ESTABLEZCA LA RECUPERACIÓN, DESCONTAMINACIÓN, DESMONTAJE, REUTILIZACIÓN, Y RECICLAJE DE VEHÍCULOS FUERA DE USO - González Luzón, Cristian Manrique (2016)
The National University of Loja in an effort to prepare professionals in the School of Law, has implemented in its graduate programs, research work for obtaining a law degree from the Courts of the Republic of Ecuador. Because it was considered desirable to run the theme "FAILURE IN COOTAD, in a legal rule setting RECOVERY, decontamination, dismantling, reuse, and recycling of vehicles out of use". The life vehicles is an issue of great importance that has emerged in recent years because this type of waste is not treated properly appearing increasingly canchones or patios of life vehicles has ceased as a consequence large numbers of vehicles who do not receive appropriate treatment, which was established as a general goal: Making a legal, doctrinal and field on the impact study has not recovery, decontamination, dismantling, reuse and proper recycling of vehicles out of use, comparing with existing laws in other countries. The investigation began with the completion of a legal review of the Constitution concerning the right of the population to live in a healthy environment also determine whether the municipalities are complying with the provisions of Art. 264 paragraph 4 of the Constitution, regarding the competences that the autonomous governments Municipal, proceeded to investigate the consequences that cause life vehicles not being treated properly and so subsequently establish a legal proposal for recycling and give proper treatment to life vehicles. We proceeded to the development of "The Failure in the COOTAD, a legal regulation stipulating the recovery, decontamination, dismantling, reuse, and recycling of life vehicles"; comprising research into the following topics: "Garbage" Garbage Types", "Life Vehicles", "Components and life cycle of vehicles out of use", "Problems generated by life vehicles" "Benefits of recovery of vehicles out of use", "Companies that recover, decontaminated, They clear, reuse, and recycle the Life Vehicles", "The Recovery of-life vehicles in Ecuador", "The Treatment of life vehicles in the city of Loja”, “The Department of Health Loja Municipal Government", "The Landfill Loja", "International Environmental Law", "Ecuadorian Environmental Law", "Ministry Environment", " Comparative Law regarding the management of Life Vehicles" During the research process it was necessary to use some methods: scientific, historical, deductive and inductive. Following this analysis and synthesis of all investigated it was made also two techniques were used: the survey and interviews, the results of which were necessary for the performance of critical analysis of the problem and verification of each of the objectives proposed in the thesis project. Finally, we proceeded to the implementation of the conclusions with their recommendations, so that a standard for the management of life vehicles is established.